Transporter Gene Regulation in Sandwich Cultured Human Hepatocytes Through the Activation of Constitutive Androstane Receptor (CAR) or Aryl Hydrocarbon Receptor (AhR) - Niu, Congrong; Smith, Bill; Lai, Yurong (Frontiers in Pharmacology, 2021)
The induction potentials of ligand-activited nuclear receptors on metabolizing enzyme genes are routinely tested for new chemical entities. However, regulations of drug transporter genes by the nuclear receptor ligands are underappreciated, especially in differentiated human hepatocyte cultures. In this study, gene induction by the ligands of constitutive androstane receptor (CAR) and aryl-hydrocarbon receptor (AhR) was characterized in sandwich-cultured human hepatocytes (SCHH) from multiple donors. The cells were treated with 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD), omeprazole (OP), 6-(4-chlorophenyl)imidazo[2,1-b][1,3]thiazole-5-carbaldehyde O-(3,4-dichlorobenzyl)oxime (CITCO) and phenobarbital (PB) for three days. RNA samples were analyzed by qRT-PCR method. As expected, CITCO, the direct activator, and PB, the indirect activator of CAR, induced CYP3A4 (31 and 40-fold), CYP2B6 (24 and 28-fold) and UGT1A1 (2.9 and 4.2-fold), respectively. Conversely, TCDD and OP, the activators of AhR, induced CYP1A1(38 and 37-fold), and UGT1A1 (4.3 and 5.0-fold), repectively. In addition, OP but not TCDD induced CY3A4 by about 61-fold. Twenty-four hepatic drug transporter genes were characterized, and of those, SLC51B was induced the most by PB and OP by about 3.3 and 6.5 fold, respectively. Marginal inductions (about 2-fold) of SLC47A1 and SLCO4C1 genes by PB, and ABCG2 gene by TCDD were observed. In contrast, SLC10A1 gene was supressed about 2-fold by TCDD and CITCO. While clinical relavence of SLC51B gene induction or SLC10A1 gene supression warrants further investigation, the results verified that the assessment of transporter gene inductions are not required for new drug entities, when a drug does not remarkably induce metabolizing enzyme genes by CAR and AhR activators.